Ἰφιάνασσα: A Lost Homeric Reading in Lucian? - Kazanskaya, Maria N. (Hyperboreus, 2021)
The article examines Lucian’s source for the name of the Nereid in DMar. 14, Iphianassa (Ἰφιάνασσα). This name does not appear in the two classical lists of Nereids in Homer (Il. 18. 37–49) and in Hesiod (Th. 240–264), from which Lucian drew the names of all other Nereids of his Dialogi marini, and Lucian is the sole ancient source to mention a Nereid by that name. This led scholars to suspect that the name may be due to a lapsus memoriae or to Lucian’s use of a corrupt text, or that it might have even been invented by him. The article shows that, as with other Nereids, the name must go back to the Homeric or Hesiodic catalogue of the Nereids, and that Ἰφιάνασσα could be due to a variant reading in Lucian’s copy of the Iliad that had *Ἰάνειρα καὶ Ἰφιάνασσα instead of Homer’s Ἰάνειρά τε καὶ Ἰάνασσα (Il. 18. 47). This would not be the only example that Lucian preserves a reading otherwise unattested in the Homeric manuscripts (cf. his quotation of Il. 13. 731 in De salt. 23 and his rendering of Od. 5. 292 in Char. 7).